O problema do mal : Rousseau e a tradição filosófica cristã - Jovenildo Ferreira dos Santos (2023)
The aim of this work is to briefly outline an historical overview of theodicy in the philosophical tradition after Christianity, taking a closer look at the debate that opposed Jean-Jacques Rousseau, (1712-1778) and Voltaire (1694-1778) on this issue. The debate had as its starting point the Lisbon earthquake in 1755. By means of a brief exposition of some of the main authors who dealt with the topic, we propose to examine the problem of evil in the history of philosophy in view of pointing out some the of novelties brought by Rousseau.